Identification of molecular difference of papaya hermaphrodite with males using SNP (single nucleotide polymorphism) and development of SNAP markers - Noflindawat; Anwar, Aswaldi; Sutanto, Agus; Sutanto, Yusniwati (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to obtain a SNAP marker that can differentiate male crops with hermaphrodite ones. This research has been conducted in the Quality Testing Laboratory of the Indonesian Tropical Fruit Research Institute, Solok West Sumatera from January to December 2019. The research used local papaya crops and papaya Merah Delima, DNA isolation derived from plants that have been fruitful as a reference plant, perform sequencing DNA genome papaya and data processing sequencing result in alignment and Identify single nucleotide polymorphisms (SNP) to further design the primary single nucleotide cation polymorphisms (SNAP) over the web. SNAPPER and perform primary optimization SNAP.The results of the second primary optimization of SNAP showed different amplification patterns where the sample of the male plant with hermaphrodite, in the sample of the male crop amplification pattern band appears on the primary reference, the female plant does not appear pattern Amplification, while the band’s hermaphrodite crop appears on the alternate primer.Both primary SNAP can be used as a marking that distinguishes the female, male and hermaphrodite plants.